MANAJEMEN BERBASIS SEKOLAH (KONSEP MANAJEMEN PENINGKATAN MUTU PENDIDIKAN) - Huliatunisa, Yayah; Magdalena, Ina; Khairunnisa, Khairunnisa (MAP (Jurnal Manajemen dan Administrasi Publik), 2025)
School Based Management (MBS) is an effort to open up opportunities and opportunities to improve and increase the quality of education, how education management can be reorganized to be more more effective and efficient based on the characteristics of each region. This research aims to study it authentically, emphasizing a holistic understanding of the management concept of improving the quality of education through MBS. Using a descriptive method, a literature review type of study. Data comes from nine scientific articles published in 2024, and nationally accredited. (content analysis) is used as a method of analyzing the data result obtained by researchers. Three steps are used in the data validity testing process, namely: trustworthiness, transferability, and research dependence on the data obtained. The result of the article review found that the MBS program has the potential to improve the quality of education, through activities: school principal training as a development effort, teacher participation, and community/school committee involvement in quality school programs, the preparation of: (RIPS) School Development Master Plan, (RAPBS) Plan School Revenue and Expenditure Budget, School self-evaluation and supervision of the school principal as an effort to optimize the strategic role and independence of the school.